Bridging the Gaps between Democracy and Democratic Governance in Nigeria: A Comparative Analysis - Okibe, Hyginus Banko; Mokuye, Chukwuwinke Smart (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
This paper critically examined the gaps between democratic governance and the notion of democracy. It applied the secondary sources of data collection, used both the historical and the descriptive approaches in the analyses, and adopted the Social Contract Theory, to explain how representative democratic system works. The findings show a remarkable and vivid difference between the concept of democracy and the practice of democracy. It further identified a number of factors that inhibit democratic practice, such as corrosive politics that perch on exclusion and pervasive corruption, among others. It results in lack of coordinated political development process. The study concludes that the present democratic practice in Nigeria simply professes the concept and has not actually conformed to global best practices.